Electrical Stimulation of Acute Fractures: A Narrative Review of Stimulation Protocols and Device Specifications - Nicksic, Peter J.; Donnelly, D’Andrea T.; Verma, Nishant; Setiz, Allison J.; Shoffstall, Andrew J.; Ludwig, Kip A.; Dingle, Aaron M.; Poore, Samuel O. (Frontiers in Bioengineering and Biotechnology, 2022)
Orthopedic fractures have a significant impact on patients in the form of economic loss and functional impairment. Beyond the standard methods of reduction and fixation, one adjunct that has been explored since the late 1970s is electrical stimulation. Despite robust evidence for efficacy in the preclinical arena, human trials have mixed results, and this technology is not widely accepted. The purpose of this review is to examine the body of literature supporting electrical stimulation for the purpose of fracture healing in humans with an emphasis on device specifications and stimulation protocols and delineate a minimum reporting checklist for future studies of this type. We have isolated 12 studies that pertain to the administration of electrical stimulation for the purpose of augmenting fracture healing in humans. Of these, one was a direct current electrical stimulation study. Six studies utilized pulsed electromagnetic field therapy and five used capacitive coupling. When examining these studies, the device specifications were heterogenous and often incomplete in what they reported, which rendered studies unrepeatable. The stimulation protocols also varied greatly study to study. To demonstrate efficacy of electrical stimulation for fractures, the authors recommend isolating a fracture type that is prone to nonunion to maximize the electrical stimulation effect, a homogenous study population so as to not dilute the effect of electrical stimulation, and increasing scientific rigor in the form of pre-registration, blinding, and sham controls. Finally, we introduce the critical components of minimum device specification reporting for repeatability of studies of this type.